2022
DOI: 10.5194/essd-14-2681-2022
|View full text |Cite
|
Sign up to set email alerts
|

New gridded dataset of rainfall erosivity (1950–2020) on the Tibetan Plateau

Abstract: Abstract. The risk of water erosion on the Tibetan Plateau (TP), a typical fragile ecological area, is increasing with climate change. A rainfall erosivity map is useful for understanding the spatiotemporal pattern of rainfall erosivity and identifying hot spots of soil erosion. This study generates an annual gridded rainfall erosivity dataset on a 0.25∘ grid for the TP in 1950–2020. The 1 min precipitation observations at 1787 weather stations for 7 years and 0.25∘ hourly European Center for Medium-Range Weat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…Various studies show a high correlation between the extreme rainfall (>99th) obtained from SPPs with rain gauge adjustment and observed stations in South America [66,86]; accordingly, their spatial distribution shows a good correlation with the RE estimate [38,51,87]. Therefore, there is evidence of using hourly rainfall from IMERGF to estimate RE-IMERGF, with respective correction-based RE-AWS.…”
Section: Construction and Validation Of Rementioning
confidence: 91%
See 2 more Smart Citations
“…Various studies show a high correlation between the extreme rainfall (>99th) obtained from SPPs with rain gauge adjustment and observed stations in South America [66,86]; accordingly, their spatial distribution shows a good correlation with the RE estimate [38,51,87]. Therefore, there is evidence of using hourly rainfall from IMERGF to estimate RE-IMERGF, with respective correction-based RE-AWS.…”
Section: Construction and Validation Of Rementioning
confidence: 91%
“…Several studies identified a high correlation in the spatiotemporal variability between precipitation and RE [23,51,63]; therefore, the correction of RE-IMERGF was performed by rescaling precipitation with observed data, for each independent pixel, using an annual factor average by season. By extending the approach of Chen et al [51], the correction process was as follows: (i) obtainment of the calibration factor by grouping the monthly series at the seasonal level (summer, autumn, winter, and spring) in the same period, 2015-2020; (ii) employ a linear regression between the point-gridded values from RE-AWS and RE-IMERGF in the four seasonal periods to obtain the slope of each linear model defined as the seasonal multiplicative factor (FME); (iii) spatial interpolation of the FME point values by using the inverse distance weighted interpolation (IDW) method, at the same native spatial resolution of IMERGF (0.1 • ); (iv) spatial aggregation applied to reduce the spatial resolution from 0.1 • to 0.25 • , with the aim of avoiding spatial inconsistencies as a consequence of the high variability of the multiply factor; (v) and finally, PISCO_reed was obtained as a result of multiplying RE-IMERGF by the FME maps. The validation was realised at the pixel level with the observed data from RE-AWS during the common period, 2015-2020.…”
Section: Construction and Validation Of Rementioning
confidence: 99%
See 1 more Smart Citation
“…The spatial and temporal distribution of RE in China varies. Average RE on the Tibetan Plateau decreases from the southeast to the northwest, and the average RE has significantly increased [30,31], which is associated with the recovery of vegetation in recent years and reduction in sand transport on the Loess Plateau [32]. The degree of rainfall erosion in South China varies from season to season, and the erosivity of annual and seasonal rainfall has increased [33].…”
Section: Introductionmentioning
confidence: 99%
“…Yue et al [18] used hourly precipitation from 2381 stations in China and applied universal kriging interpolation to map 1 km average annual RE in China's regions from 1991 to 2020. Chen et al [27,28] combined weather station data with ERA5 data to calculate RE on the TP from 1950 to 2020, their results showing that the accuracy was influenced by the density of the stations. However, due to the varied topography of the TP with elevations ranging from 80 to 8653 m and limits imposed by geographic and transportation conditions, weather stations are concentrated in eastern areas with more human activities and lower elevations, which could result in the uncertain results for western and high-altitude areas.…”
Section: Introductionmentioning
confidence: 99%